ANALYSE DES EFFLUENTS DE DIFFÉRENTS TYPES D’UNITÉS DE RAFFINAGE AU NIVEAU DE LA RAFFINERIE SAMIR (MAROC) - Kada, Naoual; Bahhou, Jamila; M’haidra, Abdellatif; El Hassouni, Mohamed (European Scientific Journal, ESJ, 2014)
The SAMIR refinery uses atmospheric distillation and vacuum distillation to treat crude oil. In our work, we first analyzed the composition of the effluents coming from Top1, Top2 and Top3 units that underwent atmospheric distillation and effluents from CHL, U101 and U103 units that underwent the vacuum distillation. The results we obtained showed that vacuum distillation generates less pollutant than the atmospheric one. On this basis, we studied the whole effluent treatment system at SAMIR which follows two steps: - A physicochemical treatment: deoiling, decantation and coagulationflocculation that allows the decrease of different pollution parameter that goes to 25% for BOD5, 22% for COD and 58% for the TSS. - A biological treatment that purifies the resulting effluents of the physicochemical treatment. The results of the analysis show that the two successive treatments enable the SAMIR to obtain final effluents that are very close to the norms in effect.